2021
DOI: 10.1007/s12016-021-08900-2
|View full text |Cite
|
Sign up to set email alerts
|

Public Health Measures and the Control of COVID-19 in China

Abstract: In December 2019, the COVID-19 pandemic quickly spread throughout China and beyond, posing enormous global challenges. With prompt, vigorous, and coordinated control measures, mainland China contained the spread of the epidemic within two months and halted the epidemic in three months. Aggressive containment strategy, hierarchical management, rational reallocation of resources, efficient contact tracing, and voluntary cooperation of Chinese citizens contributed to the rapid and efficient control of the epidemi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
58
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 68 publications
(62 citation statements)
references
References 34 publications
2
58
0
2
Order By: Relevance
“…The first country to introduce a nationwide system involving COVID-19-related QR codes was China. In summer 2020, this system was tested in Fujian province [ 67 ], while in 2021, it was employed on the national scale [ 68 , 69 ]. For the Chinese realities, a QR code system included three colors of QR codes (red: active spreader; yellow: suspicious or convalescent person; green: not infected).…”
Section: Resultsmentioning
confidence: 99%
“…The first country to introduce a nationwide system involving COVID-19-related QR codes was China. In summer 2020, this system was tested in Fujian province [ 67 ], while in 2021, it was employed on the national scale [ 68 , 69 ]. For the Chinese realities, a QR code system included three colors of QR codes (red: active spreader; yellow: suspicious or convalescent person; green: not infected).…”
Section: Resultsmentioning
confidence: 99%
“…Secondary care hospitals in IPC have limited human and material resources, making some core components difficult to implement. Our [15,16]. A median score of 85 to 100 indicated that IPC programs and guidelines are widely established in China.…”
Section: Discussionmentioning
confidence: 99%
“…At the same time, legal measures applied to companies, such as circuit breaker measures, can reduce the number of imported cases effectively, as suggested by the experience of Mainland China. 59 The measure can also motivate the conveyance operators to actively comply with the destination government’s disease-prevention regulations. Meanwhile, some actions are necessary to reduce the costs of these penalties, including (1) fully involving and consulting travellers before making any changes to disease regulations, (2) clearly and concisely informing travellers about the details of related regulations and (3) assessing the effectiveness and potential impacts of these penalties through an evidence-based approach.…”
Section: Recommendations For Implementing Travel Restrictionsmentioning
confidence: 99%
“…Imposing legal penalties such as fines or imprisonment may effectively prevent travellers from breaking quarantine orders (eg, leaving the quarantine facility without permission or refusing to take the COVID-19 test). At the same time, legal measures applied to companies, such as circuit breaker measures, can reduce the number of imported cases effectively, as suggested by the experience of Mainland China 59. The measure can also motivate the conveyance operators to actively comply with the destination government’s disease-prevention regulations.…”
Section: Recommendations For Implementing Travel Restrictionsmentioning
confidence: 99%